2022
DOI: 10.1111/jac.12602
|View full text |Cite
|
Sign up to set email alerts
|

Functional contribution of two perennial grasses to enhance pasture production and drought resistance under a leaf regrowth stage defoliation criterion

Abstract: Lolium perenne L. (Lp) is the main pasture species in New Zealand, but climate change increases the likelihood of drought during summer and consequently lowers its growth rates. Bromus valdivianus Phil. (Bv) tolerates better the summer soil water restriction, but its competitiveness in a diverse pasture relates to the defoliation management and soil moisture levels. The performance of both species in terms of production, persistence and feed quality across seasons under different defoliation regimens was evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 74 publications
1
3
0
Order By: Relevance
“…Because PR grasses are drought tolerant, have small leaf areas, and are drought resistant (Lucas et al, 2013), perennial grasses such as Salicaceae and Lithospermum and PRs, as well as ABs, increased under grazing (Figure 3). Consistent with other studies, our study demonstrated that the 5-year grazing prohibition effectively increased the species diversity and coverage (Figures 2 and 7) by protecting grassland vegetation and soil from destruction (García-Favre et al, 2023;Xia et al, 2022), which is conducive to efficient grassland management and utilization. Meanwhile, grazing inhibition increased perennial grasses such as L. chinensis, Stipa krylovii, and C. squarrosa (Figure 3).…”
Section: Impact Of Grazing Disturbance On Grassland Vegetation Commun...supporting
confidence: 91%
“…Because PR grasses are drought tolerant, have small leaf areas, and are drought resistant (Lucas et al, 2013), perennial grasses such as Salicaceae and Lithospermum and PRs, as well as ABs, increased under grazing (Figure 3). Consistent with other studies, our study demonstrated that the 5-year grazing prohibition effectively increased the species diversity and coverage (Figures 2 and 7) by protecting grassland vegetation and soil from destruction (García-Favre et al, 2023;Xia et al, 2022), which is conducive to efficient grassland management and utilization. Meanwhile, grazing inhibition increased perennial grasses such as L. chinensis, Stipa krylovii, and C. squarrosa (Figure 3).…”
Section: Impact Of Grazing Disturbance On Grassland Vegetation Commun...supporting
confidence: 91%
“…There is scarce information on nutritional strategies to cope with climate change (adaptation) and in turn, reduce the N partitioning and excretion of pasture-based dairy heifers (mitigation of climate change). Furthermore, the current study evaluated growth performance and N partitioning of heifers grazing a traditional pasture species (Lp) and a promising native species, Bv, which tolerates the summer soil water restriction better than Lp, being an alternative as climate change increases the likelihood of drought during summer and consequently lowers its growth rates [37].…”
Section: Discussionmentioning
confidence: 99%
“…Previously, it has been shown that mixtures dominated by perennial ryegrass and pasture brome can have similar attributes to Lp pastures in terms of DM yield [54] and fermentation in the rumen [38,39]. More recently, García-Favre et al [37] observed a synergy when combining Lp and Bv by increasing DM yield by 15% compared with Lp, mainly due to an increase in production in spring and summer. In spring, there was a complementarity growth between both species, while during summer/early autumn, the production resulted in the higher participation of Bv as well as a greater root biomass at a depth of 31-70 cm.…”
Section: Implications Of the Studymentioning
confidence: 99%
“…Water stress has been shown to reduce tiller survival in tall fescue swards (Assuero et al., 2002; West et al., 1993), particularly in Mediterranean climates (Norton et al., 2016; Poirier et al., 2012). Tolerance to water stress associated with large root systems has been proposed as a relevant trait to explain vegetative pasture persistence (García‐Favre et al., 2022; Garwood & Sinclair, 1979; Langworthy et al., 2019; Nie et al., 2008). Deep and functional root systems may delay water stress by providing a continuous supply of water during droughts (Garwood & Sinclair, 1979; Ludlow et al., 1989; Volaire et al., 1998), and thus strengthen dehydration avoidance in summer‐dry environments (Norton et al., 2016).…”
Section: Introductionmentioning
confidence: 99%